Serological Response to BNT162b2 Anti-SARS-CoV-2 Vaccination in Patients with Inflammatory Rheumatic Diseases: Results From the RHEUVAX Cohort - Mauro, Daniele; Ciancio, Antonio; Di Vico, Claudio; Passariello, Luana; Rozza, Gelsomina; Pasquale, Maria Dora; Pantano, Ilenia; Cannistrà, Carlo; Bucci, Laura; Scriffignano, Silvia; Riccio, Flavia; Patrone, Martina; et al. (Frontiers in Immunology, 2022)
Objective: Immunological alteration associated with Immune Rheumatic Diseases (IRD) and immunosuppressive medications may impair the response to vaccination. In the light of the current COVID19 epidemic and the availability of effective vaccines, this study aims to identify predictors of non-response to anti-SARS-CoV-2 vaccines. Methods: IRD and age and sex-matched controls volunteer among the health professionals (CTRL) who underwent vaccination with two doses of BNT162b2 were recruited for this study. Anti-Trimeric Spike protein antibodies were assayed eight ± one weeks after the second vaccine dose. Univariate and logistic regression analyses were performed to identify predictors of non-response and low antibody titers. Results: Samples were obtained from 237 IRD patients (m/f 73/164, mean age 57, CI 95% [56-59]): 4 autoinflammatory diseases (AI), 62 connective tissue diseases (CTD), 86 rheumatoid arthritis (RA), 71 spondylarthritis (SpA) and 14 vasculitis (Vsc). 232 CTRL were recruited (m/f 71/161, mean age 57, CI 95% [56-58]). Globally, IRD had a lower seroconversion rate (88.6% vs 99.6%, CI 95% OR [1.61-5.73], p<0.001) and lower antibody titer compared to controls (median (IQR) 403 (131.5-1012) vs 1160 (702.5-1675), p<0.001). After logistic regression, age, corticosteroid (CCS), Abatacept, and Mycophenolate Mofetil (MMF) use were predictors of non-response. Lower antibody titer was associated with the use of MMF, ABA, CCS, Rituximab, Tumour necrosis factor inhibitor, JAK inhibitors and higher age. Conclusion: The response to anti-SARS-CoV-2 vaccines is often impaired in IRD patients under treatment and may pose them at higher risk of severe COVID-19. Specific vaccination protocols are desirable for these patients.